2001
DOI: 10.1161/hc2601.093272
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Filters

Abstract: A lthough percutaneous, catheter-based treatment for atherosclerotic arterial obstruction began in the peripheral circulation, usage became widespread only after coronary application. The procedure's abilities to relieve angina and either spontaneous or provoked myocardial ischemia and to achieve prompt reperfusion in myocardial infarction are well-documented. 1 Even selected patients with advanced, multivessel coronary disease can expect outcomes similar to those provided by the more invasive bypass surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…However, we could not exclude the development of a stroke even in the setting of distal protection. 25 In a recently published article, Roubin et al 2 reported the important reduction of periprocedural complication rate over 5 years of experience from 9.3% in the first year to 4.3% in the fifth year. This was probably due to refinement of stenting techniques and newly developed equipment.…”
Section: Angelini Et Al Atheroembolism After Carotid Stenting 459mentioning
confidence: 99%
See 1 more Smart Citation
“…However, we could not exclude the development of a stroke even in the setting of distal protection. 25 In a recently published article, Roubin et al 2 reported the important reduction of periprocedural complication rate over 5 years of experience from 9.3% in the first year to 4.3% in the fifth year. This was probably due to refinement of stenting techniques and newly developed equipment.…”
Section: Angelini Et Al Atheroembolism After Carotid Stenting 459mentioning
confidence: 99%
“…Furthermore, particles of vasoactive substances contained within plaque or thrombus could cause intense, prolonged vasospasm and subsequent cerebral infarction. 25 The histopathologic analysis showed that retrieved material consists of dislocated debris featuring atheroembolism as a consequence of atheromatous plaque squeezing and rupture occurring during carotid stent implantation. This result confirms the data of previously reported studies evaluating different emboli protection devices during percutaneous intravascular interventions.…”
Section: Angelini Et Al Atheroembolism After Carotid Stenting 459mentioning
confidence: 99%